Effects of Landscape Age and Salinity on Plant Community Composition and Productivity in Opportunistic and Constructed Wetlands in the Athabasca Oil Sands Region, Alberta - Mombourquette, Ashlee Dawn (Graduate Studies, 2023)
Wetlands comprise 65% of the Athabasca Oil Sands Region (AOSR) surface mineable area and thus support diverse flora (approximately 400 species in Alberta). Due to increased anthropogenic land disturbance activities such as bitumen extraction, reclamation of surface mineable areas will also increase. The resulting reclaimed areas will tend to be sodium-enriched compared to pre-disturbance landscapes. In this thesis, forty young (<40 years old) stratified-randomly selected wetlands were sampled on reclaimed landscapes at Syncrude’s Mildred Lake lease and from reference wetlands in adjacent areas in the AOSR to determine how salinity and age influence the vegetation community composition, and the biomass of six dominant wetland plant species (Carex aquatilis, Calamagrostis canadensis, Carex atherodes, Carex utriculata, Schoenoplectus tabernaemontani, and Typha latifolia) found on reclaimed and reference landscapes. Wetland vegetation communities on reclaimed landscapes differed from those on reference landscapes; however, landscape type had no impact on the biomass of the dominant plant species. Vegetation communities varied along a salinity gradient; species richness was negatively associated with salinity, and vegetative species abundance (percent cover) was lowest in freshwater wetlands and highest in moderately brackish wetlands. Species richness did not differ among wetland classes. However, vegetative species abundance was significantly different among age classes. The biomass produced by each dominant species did not vary with respect to a gradient of salinity or among wetlands of different age classes. These findings may provide a useful frame of reference against which to compare vegetation communities that may be observed in wetlands forming on reclaimed landscapes.